Ho boulomenos and Athenian public lawsuits from the death of Alexander the Great to the first century B.C.: evidence of the survival of a classical legal institution in Hellenistic Athens (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
The practice of granting any willing individual the right to denounce serious offences has been directly linked to the legal system of Athens. Although the literary and epigraphic material concerning the law of post-classical Athens is less informative than that of the classical period, references to procedures initiated by ho boulomenos (“anyone who wishes”) from the late fourth century B.C. to the early years of Augustus’ reign show that the Athenian legal system continued to provide for the right of volunteers to denounce offences affecting important aspects of social and political life, such as acts against the polis constitution, religious affairs or the use of proper weights and measures. This article highlights the phenomenon of public lawsuits in Athens during the Hellenistic period by presenting all relevant literary and epigraphic references and demonstrating the continuing importance of this type of prosecution for the Athenian state.
Keywords: Athenian law; ho boulomenos; Athenian legal procedure; public lawsuits; Hellenistic Athens; early Roman Athens